2013
DOI: 10.1016/j.ygyno.2013.07.092
|View full text |Cite
|
Sign up to set email alerts
|

Self-collection for high-risk HPV detection in Brazilian women using the careHPV™ test

Abstract: Self-sampled and health professional-sampled vaginal/cervical specimens did not differ in their rates of detection of hr-HPV. Therefore, HPV DNA testing in self-sampled vaginal cells is an alternative to primary screening in low-resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 13 publications
(25 reference statements)
2
31
2
1
Order By: Relevance
“…Specialized training and education are not required to run the test. It has been evaluated in multiple countries and found that careHPV is a sensitive and reasonably specific screening test for cervical precancer and cancer (7)(8)(9)(10)(11)(12). In 2012, the China Food and Drug Administration approved this test for cervical cancer screening (13).…”
mentioning
confidence: 99%
“…Specialized training and education are not required to run the test. It has been evaluated in multiple countries and found that careHPV is a sensitive and reasonably specific screening test for cervical precancer and cancer (7)(8)(9)(10)(11)(12). In 2012, the China Food and Drug Administration approved this test for cervical cancer screening (13).…”
mentioning
confidence: 99%
“…The results of the current study are consistent with those of other studies regarding HPV detection in Brazilian women. de Aguiar Original Article et al, 25 Lorenzi et al, 19 Rosa et al, 26 and Nonnenmacher et al 27 reported HPV prevalence rates of 10.5%, 12.3%, 12.3%, and 15%, respectively. The majority of these women lived in rural or remote areas of Brazil and experienced difficulties in accessing medical care or the heath assistance infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…This method can detect 14 types of hr-HPV (types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 66, and 68), and >90 specimens can be processed within 2.5 hours. 12,13,19 …”
Section: Carehpv Testmentioning
confidence: 99%
See 2 more Smart Citations